2011
DOI: 10.1039/c0an00826e
|View full text |Cite
|
Sign up to set email alerts
|

Use of thermally annealed multilayer gold nanoparticle films in combination analysis of localized surface plasmon resonance sensing and MALDI mass spectrometry

Abstract: A self-assembled film of gold nanoparticles (AuNPs) with a raspberry-like morphology was prepared on a glass plate by the layer-by-layer thermal annealing of multilayer films of AuNPs. It was possible to control the morphology of the obtained films of AuNPs by changing the annealing temperature, duration of annealing, and number of layers. On investigating the plasmonic properties of these films, we found that AuNP films with a raspberry-like morphology yielded the highest refractive index unit, which is a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The calcinated AuNP film displays well-defined absorption spectra and good LSPR sensitivity for spherical nanoparticles, with a bulk sensitivity of 84 ± 10 nm/RIU obtained with different solvents (Figure 2 a), which is equivalent to that of other reported solid-bound AuNP structures. 23 The differential extinction spectrum approach was employed for data analysis so that refractive index sensitivities may be evaluated at any given wavelength, rather than limited at the extinction peaks. 24 For calcinated monolayer AuNPs, we observed that wavelengths higher than the initial peak display higher sensitivities, with the sensitivity of 0.106 NEU/RIU at 570 nm increasing to 0.497 NEU/RIU at 600 nm (Figure 2 b).…”
mentioning
confidence: 99%
“…The calcinated AuNP film displays well-defined absorption spectra and good LSPR sensitivity for spherical nanoparticles, with a bulk sensitivity of 84 ± 10 nm/RIU obtained with different solvents (Figure 2 a), which is equivalent to that of other reported solid-bound AuNP structures. 23 The differential extinction spectrum approach was employed for data analysis so that refractive index sensitivities may be evaluated at any given wavelength, rather than limited at the extinction peaks. 24 For calcinated monolayer AuNPs, we observed that wavelengths higher than the initial peak display higher sensitivities, with the sensitivity of 0.106 NEU/RIU at 570 nm increasing to 0.497 NEU/RIU at 600 nm (Figure 2 b).…”
mentioning
confidence: 99%
“…Several means for incorporating nanomaterials in LC systems were described in Section . These methods included covalent immobilization, adsorption, entrapment, and the synthesis or direct development of nanomaterials as part of a chromatographic support . The direct use of some nanomaterials as LC supports has also been possible in a few situations .…”
Section: Resultsmentioning
confidence: 99%
“…Another strategy that has been used for charged nanoparticles has been to adsorb them onto a support or surface by means of electrostatic interactions . Immobilization through adsorption is often easier to carry out than covalent immobilization, although it can result in lower stability for the stationary phase and some loss in reproducibility when a column containing such a material is used over long periods of time .…”
Section: Incorporation or Immobilization Of Nanomaterials In Lc Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermally annealed multilayer Au nanoparticle films were also prepared from Au nanoparticles synthesized in solution. 32 Instead of using interface-assisted assembly, multilayer gold nanoparticle films were formed on substrates using layer-by-layer thermal annealing techniques. The sensing platform built from multilayer Au nanoparticle films reached picomolar detection limits for the LSPR sensing of lysozyme in a buffer solution.…”
Section: Assembly On Surfacesmentioning
confidence: 99%